Air-stable NiFeCrOx selective absorber for mid-to-high temperature application. (March 2015) - Ding, Dawei; Wu, Haodong; Yu, Xiaojuan
Highlights: Textured NiFeCrO x film was in-situ synthesized on the NiFeCr alloy surface. Absorptance α > 0.9 and emittance ε ⩽ 0.1 was achieved for this novel selective absorber. The selective absorber was thermally stable up to 300 °C for 300 h in air. Abstract: Textured NiFeCrO x film has been synthesized by electrochemically treating a Fe–Cr–Ni alloy surface. The special surface configuration was favorable for light selective absorption, absorptance exceeding 0.9 and emittance near 0.1 were achieved. The thermal stability of this film was tested by heat treatment at 300 °C for 300 h in air. Optical performance was found no obvious changes. AFM and Raman spectroscopy were applied to investigate the detailed information of surface structure and chemical composition. It was found that the effective absorbing materials were mainly oxidation-resistant Cr2 O3 and NiFe2 O4 spinel. Both the chemical composition and urchin-like surface structure showed excellent stability at 300 °C in air. The considerable optical performance and thermal stability enabled the NiFeCrO x film promising candidate for mid-to-high temperature photo-thermal conversion material.